Implementation of Indonesian Islamic Family Law to Guarantee Children’s Rights - Khoiruddin Nasution; Syamruddin Nasution (Al-Jami'ah: Journal of Islamic Studies, 2021)
This paper aims to discuss and observe the legal practice of child protection, particularly, custody and the legal attitude in Muslim society and of the parents, specifically in Indonesia. Deploying a socio-legal approach, it is clear that theoretically, through a number of laws and regulations, the state has provided legal protection to children in terms of custody, as well as from violence. In practice, the legal rights to custody are hardly obtained by children in either legal decisions or executorial steps. The paper argues that the failure of this legal protection is due to the problem of case settlement in the Islamic (religious) court, which tends to be more administrative than judiciary, and that theoretically to provide justice, the work of judges must not only be certain, but also judicial. This paper also analyses the reasons why judges in Religious Courts tend to be more oriented toward administrative issues than judiciary ones. One reason is that the atmosphere of the Religious Courts (PA) now supports administrative decisions more than judicial ones.[Artikel ini membahas dan mengamati praktik hukum perlindungan anak khususnya penjagaan dan perilaku hukum pada orang tua dan masyarakat muslim di Indonesia. Terlepas dari pendekatan sosiologi hukum, secara teoritis negara memberikan perlindungan hukum pada anak dalam kerangka penjagaan dari kekerasan melalui sejumlah hukum dan peraturan. Dalam praktiknya, hak penjagaan sulit didapatkan oleh anak baik dalam bentuk putusan atau eksekusinya. Artikel ini menjelaskan bahwa kegagalan tersebut terkait dengan penyelesaian kasus di pengadilan agama, yang cenderung administratif  daripada substantif, meski secara teoritis tetap mendorong keadilan, dan kerja hakim bukan hanya memberikan kepastian hukum tetapi juga kemanfaatan. Artikel ini juga membahas alasan putusan hakim pengadilan agama cenderung berorientasi administratif  daripada substantif. Salah satu alasannya adalah atmosfir pengadilan agama yang lebih mendukung putusan administratif..]